Comparative perspectives on the origins, development and structure of Amazonian (Karipúna) French Creole - Ferreira, Jo-Anne S.; ALLEYNE, Mervyn C. (My University, 2010)
Together known as Kheuól, Karipúna French Creole (KFC) and Galibi-Marwono French Creole (GMFC) are two varieties of Amazonian French Creole (AFC) spoken in the Uaçá area of northern Amapá in Brazil. They are socio-historically and linguistically connected with and considered to be varieties of Guianese French Creole (GFC). This paper focuses on the external history of the Brazilian varieties, and compares a selection of linguistic forms across AFC with those of GFC and Antillean varieties, including nasalised vowels, the personal pronouns and the verbal markers. St. Lucian was chosen as representative of the Antillean French creoles of the South-Eastern Caribbean, including Martinique and Trinidad, whose populations have had a history of contact with those of northern Brazil since the sixteenth century. Data have been collected from both field research and archival research into secondary sources.
Keywords: Karipúna, Galibi-Marwono, French Creole, Brazil